PROFIL CERITA ANAK DAN MEDIA BONEKA TANGAN DALAM METODE BERCERITA BERKARAKTER UNTUK SISWA SD - Sulianto, Joko; Untari, Mei Fita Asri; Yulianti, Fitri (Universitas Pendidikan Indonesia, 2014)
Storytelling activities for students is a core activity that is identical to their world. In storytelling, there is the emotional closeness between students and storyteller. In this case the teachers and parents. Storytelling is a joint activity between listening activities, talking, imagining, filled with empathy closeness between the two sides. Criteria are children's stories (1) spoken / narrated by an adult, (2) figure old man and children, if any adult figure as a transmitter of right and wrong behavior, (3) themed adventure, mystery / magic, and helping , (4) the background story can be found in the place of children in real life (field, mountains, fields, markets, and home), (5) grooved / storyline straight or coherent, (6) the type of story comes from true story or a story inspired by a true story, and (7) the mandate must contain positive values. Children will imagine it as background, character, and conflict as if real or close to the child. Media Boneka Tangan appropriate to the needs of students and teachers is a medium hand puppets made of flannel and cotton fabric, medium-sized or according to the size of the hand, and has a bright color so attractive. Keywords: profiles of children's stories, media boneka tangan, elementary students.